Interpretation of Meaning in the Lyrics of a Minangkabau Regional Song with the Title “Pasan Mandeh” (Hermeneutic Study) - Habib, Ikhwanul; Masruri, Hadi (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
To understand the meaning of a text or work of art can use a hermeneutic approach. This study aims to interpret the meaning in the lyrics of a Minangkabau folk song titled "Pasan Mandeh" with a hermeneutic approach using Paul Ricoeur's theory, which outlines the steps of understanding by starting from semantic, reflexive, and existential Understanding. Ricoeur's theory was chosen because of several distinctive reasons not shared by other figures, namely Ricoeur rejected hermeneutics as a rigid and objective method. Ricoeur viewed the text as an autonomous entity independent of the author's intention, so that readers have the space to creatively appropriate meaning but are still limited by the content of the text. The research method uses a literature study and interviews. The results of the study found that the first is a semantic understanding that contains a literal understanding of meaning, and it is not deep, as in the song lyrics, where there is the use of symbols that describe the beauty of nature and life. Second is a reflexive understanding that examines meaning by adjusting the cultural context, such as using "Kato Malereang" in everyday life. The third is an existential understanding that reflects on the meaning of the song lyrics and applies the moral messages and life values channeled by the author through the song lyrics.